Case Series: Cyclops lesion - extension loss after ACL reconstruction - Dhanda, Sunita (Medknow Publications, 2010)
Localized anterior arthrofibrosis (cyclops lesion) is the second most common cause of extension loss after anterior cruciate ligament (ACL) reconstruction. We present and discuss two patients with prior ACL reconstructions, who presented with pain and loss of extension following surgery. MRI and arthroscopy of the knee revealed typical features of a cyclops lesion. The patients showed significant symptomatic improvement following arthroscopic resection of these lesions.